As naturalistic as it gets: subtitles in the English classroom in Norway - Vulchanova, Mila; Aurstad, Lisa M. G.; Kvitnes, Ingrid E. N.; Eshuis, Hendrik (Frontiers in Psychology, 2015)
This study aimed to investigate both short-term and long-term effects of exposure to original English subtitles in the context of learning English as a second language in Norwegian upper secondary/high schools (Baltova, 1999). The study was initially inspired by Mitterer and McQueen (2009) who showed that original English subtitles improved speech perception, and more generally, processing of less frequent English varieties. We ran a series of tests with two age groups, 16 year old (N = 65) and 17 year old (N=49) students. To establish a baseline, we tested all participants’ proficiency on grammar and vocabulary. In addition participants filled out a questionnaire on their linguistic background with a focus on extra-curricular activities where English might be involved (e.g., watching videos/TV, playing computer games, but also time spent reading/writing English). Both groups of 16 and 17-year-old pupils were divided into three groups each and had to watch an episode of Family Guy, a control group, who watched without subtitles and 2 experimental groups, one watching with original English subtitles, and the other with native Norwegian subtitles. Our hypothesis was that native Norwegian subtitles would aid comprehension in the younger experimental group of participants (16 year olds), whereas, in contrast, the English subtitles would be more beneficial for the older group (17 year olds). We also expected that level of proficiency would modulate this effect. To test this we administered a comprehension test measuring how well the participants understood the story. To check whether exposure to subtitles was beneficial in the long-term (d’Ydewalle and Van de Poel, 1999), we tested the same groups of participants four weeks after the first experiment. We administered a word definition task and a word recall task, both containing words that participants had been exposed to in the Family Guy video.